Fashion Figures: How Missy the Mathlete Made the Cut - Borza, Melissa A (Apress, 2017)
Missy Maker is a middle school girl who loves math and fashion. She sees math in everything she does. She tries to hide this from her friends, because she thinks it’s too geeky. Missy hears that the school math club needs more members, but she’s worried about what her friends will think if she joins, and she’s already committed to joining the fashion club. After an epic internal struggle and with the support of her peers and her quirky, loving family, Missy finds that she can be both a Mathlete and a Fashionista. Missy figures out how to bring the two clubs together to help both groups win. In the process, she discovers that she can openly excel in math and science and still be popular with her peers. She also learns how her math and science skills can help her artistic endeavors. Gain an inside perspective on what it’s like when you love math and science and happen to be a girl. Fashion Figures highlights the societal and internal pressures preteen and early-teen girls often face when they excel in these subjects, and it shows strategies for overcoming barriers to being themselves and doing what they love while still fitting in socially.